Risiko Bedah pada Pasien Dewasa dengan Tetralogi Fallot - Karina V Wilamarta; Dicky Fakhri; Jusuf Rachmat (The Indonesian Heart Association, 2007)
Background. The beneficiaries of successful pediatric cardiac surgery and cardiology increases surgical treatment in the adult population with congenital heart disease. Adults patient with Tetralogy of Fallot (TOF) will need surgery either reoperative, palliative or more commonly reparative by the time they come. Many of them face the prospect of further operations, arrhythmias, complications and if managed inappropriately will increase risk of heart failure and premature death. This study presents the early surgical results of adult TOF.Methods and results.Data were reviewed retrospectively related to the hospital course of TOF adult patients (age > 17 years) from June 1, 1998 to December 30, 2006 who require surgical treatment in National Cardiac Center - Harapan Kita, Indonesia. Most of the operations were corrective procedures (20 patients, 66.7%), followed by palliative procedures (6 patients, 20%), and reoperations (4 patients, 13.3%). Mean age at surgery was 20.87+5.49 years. There were no hospital mortality in the primary corrective group, one death (16.7) in the palliative group related to poor left ventricular function, and one death (25%) in the reoperation group related to perioperative bleeding. Follow up data of 11.73+17.68 months duration were available in 28 of 30 patients (93%) who were discharged home. Overall survival probability is higher for corrective procedures than palliative and reoperative procedures.Conclusions. Surgical treatment of TOF in adult patients proved quite save and beneficial.